ANTIVIRAL ACTIVITY OF EUPHORBIA MICROSCIADIA EXTRACT - Ramezan, M.; Behravan, J.; Arab, M. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
In traditional medicine, the extracts of different species of Euphorbia have been successfully used for the treatment of skin diseases. Therefore, the antiviral effects of Euphorbia microsciadia extracts were investigated using a plaque reduction assay. Plant material was collected, dried and ground and extracted either with methanol using a Soxhlet apparatus or by maceration in methanol. After applying several enriching stages of phage CP51, phage titration was performed to determine the phage concentration in phage lysate for specifying the dilution factor of the phage to be used as negative control for the next working stages. Then IC50 of trifluridine, as a positive control, for phage CP51 was determined. The MIC of the extracts for Bacillus cereus was determined as 1.25 and 0.5 mg/ml for Soxhlet and maceration extracts, respectively, To determine whether the extracts have the ability to inhibit the adsorption of virus to host cell, it was pre-incubated with phage CP51 for 30 min at 25ºC. The growth and reproduction of phage was inhibited by more than 50% at concentration of 1 and 0.25 mg/ml, respectively. In order to test the effects of extract on the transcription process, Bacillus cereus, phage CP51 and extract were incubated together. The growth and reproduction of phage was inhibited by more than 50% at concentration of 0.75 and 0.125 mg/ml for Soxhlet and macerated extracts, respectively. These results indicated that both extracts of E. microsciadia have considerable antiviral activity.